Genotypic variability in cotton's transpiration response under progressive soil drying - Broughton, Katrina J.; Bate, Eleanor L.; Cutler, Corey W.; Allen, Christopher N.; Thompson, Alan J. E.; Conaty, Warren C. (Frontiers in Plant Science, 2024)
Crop yields in food and fibre production systems throughout the world are significantly limited by soil water deficits. Identifying water conservation mechanisms within existing genotypes is pivotal in developing varieties with improved performance in water-limited conditions. The objective of this study was to screen Australian germplasm for variability in the transpiration response to progressive soil drying using a glasshouse dry-down experiment. It tests the hypothesis that water conservation traits may provide tolerance to water stress, particularly when combined with other drought stress traits. Three glasshouse experiments were conducted to identify whether there are differences in the fraction of transpirable soil water (FTSW) threshold values for transpiration decline among six cotton genotypes. We also assessed whether genotype dependent responses to progressive soil drying are evident from leaf-level physiology, by measurement of gas exchange parameters. Significant variation in the FTSW threshold for transpiration decline between six genotypes was found, ranging from 0.13 to 0.29. Genotypic variation in the response to soil drying was also observed from leaf level physiology, with reductions in stomatal conductance and photosynthetic rate coinciding with when the FTSW threshold was reached. Genotypes that limit transpiration at high FTSW can conserve water earlier in the season to maintain productivity during extended dry periods. Therefore, these genotypes may provide physiological traits that improve productivity in water-limited environments. This research is important as rainfall and water resources for irrigated agriculture are predicted to decline. The development of drought tolerant germplasm for the Australian cotton industry will be beneficial in the projected increasingly frequent limited water environments resulting from a changing climate.